A sliver of darkness eaudiobook Stories. - Tudor, C. J. (Random House Audio, 2022)
The debut short-story collection from the acclaimed author of The Chalk Man, hailed as “Britain’s female Stephen King” ( Daily Mail ), featuring eleven bone-chilling and mind-bending tales “All hail the queen of scream.  A Sliver of Darkness  is C. J. Tudor at her spine-tingling, nightmare-inducing best. Read it if you dare.”—Chris Whitaker,  New York Times  bestselling author of  We Begin at the End Time slips. Doomsday scenarios. Killer butterflies. C. J. Tudor’s novels are widely acclaimed for their dark, twisty suspense plots, but with A Sliver of Darkness, she pulls us even further into her dizzying imagination. In “The Lion at the Gate,” a strange piece of graffiti leads to a terrifying encounter for four school friends. In “Final Course,” the world has descended into darkness, but a group of old friends make time for one last dinner party. In “Runaway Blues,” thwarted love, revenge, and something very nasty stowed in a hat box converge. In “Gloria,” a strange girl at a service station endears herself to a coldhearted killer, but can a leopard really change its spots? And in “I’m Not Ted,” a case of mistaken identity has unforeseen fatal consequences. Riveting, macabre, and explosively original, A Sliver of Darkness is C. J. Tudor at her most wicked and uninhibited.